Społeczna gospodarka rynkowa - zasady jej funkcjonowania w ujęciu Waltera Euckena - Kicior, Karolina; Klamut, Mirosława (The Social Market Economy - Principles of its Functioning by Walter Eucken, 2008)
The aim of this article is to illustrate a theoretical basis for establishing the social market economy. The social market economy is mostly connected with Christian democracy. This phenomenon concerns especially West Germany, where this conception is part of a Christian Democratic party programme. The notion of "Wirtschafswunder" can be found in every economic dictionary all over the world. Among economists who influenced this thesis are: Walter Eucken, Franz Bohm, and K. Paul Hensel. This economic group developed "thinking in general economic categories". In literature they are called "representatives of neo-liberalism" or "class liberalism" (germ, ordoliberalism). The most important for them was social economy protection. They started from economic management. The article discusses 7 rules of Eucken concerning competition and 4 rules of economic policy. The article presents the main theories that led to the establishment of the social market economy and their creators.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 10, s. 167-181